New perspectives on Microsoft Powerpoint 2010, comprehensive - 319508 Zimmerman, Beverly B.; Zimmerman, S. Scott 319516; Pinard, Katherine T. 516770 (Boston, MA : Cengage Course Technology, 2011)
PSZJBL